Tracking infectious prions in the body fluids of deer infected with chronic wasting disease - Mathiason, Candace Kay, author; Hoover, Edward A., advisor; Avery, Anne, committee member; Bamburg, James R., committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2010)
Chronic wasting disease (CWD) is a prion disease of cervid (elk, moose and deer) with unusually high transmission efficiency. While the nidus of disease was described in a captive herd of cervid in northern Colorado/southeastern Wyoming in the late 60's, it has now been detected in both captive and free-ranging populations in 17 states and 2 Canadian provinces of North America and one Asian country. CWD is unique in being the only transmissible spongiform encephalopathy (TSE) described in a free-ranging population of animals. The etiology of CWD, like all prion diseases, is the conversion of the normal host-encoded cellular prion protein (PrPC) to an aberrantly folded protease resistant isoform (PrPRES/PrPCWD). An intriguing aspect of prion diseases is their ability to be transmitted from one organism to the next. In this dissertation work, we ask-By what means are infectious prions transmitted from one host to the next? In particular to CWD-What do infected cervids share or leave behind that contain sufficient infectious particles to initiate disease in the next cervid? We addressed this question by bioassay of body secretions and excretions- ' secreta '- (saliva, blood, urine and feces) in the native white-tailed deer host and in transgenic mice expressing the normal cervid prion protein (Tg(CerPrP) mice). Cohorts of deer were exposed by oral (PO) ingestion of 'secreta', or intraperitoneal (IP)/intravenous (IV) transfusion of blood components. To replicate a more natural/realistic exposure to CWD in which a deer might travel into a contaminated area and feed for a short period of time, an additional cohort of deer was exposed to fomites (bedding, feed and water buckets) from the suites of CWD-infected deer-without direct contact with infected deer. These variously exposed deer were monitored for a minimum of 19 months post inoculation (mo pi) for CWD infection and disease by immunohistochemical (IHC) and western blot (WB) detection of PrPCWD in serial tonsil biopsies and in multiple tissues after necropsy. Parallel studies were conducted in Tg(CerPrP) mice with the addition of an intracranial (IC) inoculation group for each body fluid. We found that sufficient infectious prions were present in the saliva, whole blood, the B cell- and platelet-enriched fractions of blood, and in fomites from infected deer premises to transmit CWD. Conversely, PrPCWD was not detected in the brain or lymphoid tissues of deer or mice inoculated with urine and feces, cell-free plasma or CD14+ monocytes from CWD-infected donor deer. The results of this work: 1) suggest that the efficient transmission of CWD may be due in part to the sharing of saliva between cervids and its deposition upon surfaces frequented by cervids; 2) establish a hematogenous dissemination of infectious prions in CWD associated with the cellular fraction of blood- in particular B cells and platelets— in CWD-infected deer; 3) extend previous work localizing PrPCWD to the interface of follicular B cells and dendritic cells; 4) provide insights to PrPCWD trafficking and CWD pathogenesis; and 5) establish saliva and blood cells as viable substrates for PrPCWD antemortem detection.
Keywords: Chronic wasting disease; Prion diseases in animals; Deer -- Diseases